Teratogenic effects of imidacloprid in rats: mechanistic role of oxidative stress - Borai El-Borai, Nermeen; Said Hadad, Seham; Kamal Khalifa, Hanem (International Journal of Pharmacology and Toxicology, 2019)
Extensive use of imidacloprid (IMI) insecticide in the agro-vet practices leads to continuous animal and human exposure. Exposure of pregnant dams to such insecticides results in fetal malformations. In the light of this, the present study was designed to investigate the teratogenic effects of two different doses of IMI and the possible mechanistic role of oxidative stress. Fifteen pregnant females were randomly divided into three equal groups and orally treated daily during organogenesis period (6-15th GD), control (distilled water), LD-IMI (45 mg/kg) and HD-IMI (90 mg/kg). All pregnant dams were exposed to caesarean section on GD 20. Exposure to IMI induced significant increase in the percentage of resorptions at high-dose with significant reduction of fetal and placental weights in a dose-dependent manner. External fetal morphological abnormalities were recorded only at high-dose while several visceral abnormalities were observed in fetuses at low- and high-doses. Significant increases in the percentages of fetal skeletal malformations were recorded only in the high-dose group. Significant changes in MDA, GSH levels and CAT activity with insignificant change in the level of H2O2 were recorded only in placentae of LD-IMI group. However, all these parameters recorded significant changes in serum of dams, placentae and liver of fetuses at high-dose. In conclusion, exposure of pregnant rats to IMI, particularly at higher-dose, during the period of organogenesis induced fetal teratogenic effects that may be related to its maternal and fetal oxidative damaging impacts.Â Â Â